Answer:
a. y=x, x-axis, y=x, y-axis
Explanation:
We have,
'Reflection across x-axis changes (x,y) to (x,-y)'
'Reflection across y-axis changes (x,y) to (-x,y)'
'Reflection across y=x changes (x,y) to (y,x)'
As, ABCD have co-ordinates A(1,-1), B(4,-1), C(2,-2) and D(3,-2).
We see that, on applying the reflections in the sequence 'y=x, x-axis, y=x, y-axis', the following table is obtained,
y=x x-axis y=x y-axis
A=(1,-1) (-1,1) (-1,-1) (-1,-1) (1,-1)
B=(4,-1) (-1,4) (-1,-4) (-4,-1) (4,-1)
C=(2,-2) (-2,2) (-2,-2) (-2,-2) (2,-2)
D=(3,-2) (-2,3) (-2,-3) (-3,-2) (3,-2)
Hence, the sequence 'y=x, x-axis, y=x, y-axis' maps ABCD onto itself.